1992
DOI: 10.24266/0738-2898-10.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Nontarget Herbicide Losses from Application of Granular Ronstar to Container Nurseries

Abstract: With empty containers, nontarget herbicide loss was 23 percent when the containers were spaced container to container. Spacing the containers on 20 (8 in) and 30 cm (12 in) centers resulted in nontarget losses of 51 and 80 percent loss respectively. Nontarget losses were similar when a dense canopy plant (Rhododendron × ‘Trouper’) and an open canopy plant (Berberis thunbergii ‘Crimson Pygmy’) were spaced container to container or on 20 (8 in) or 30 cm (12 in) spacings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Wide spacing allows more of a broadcast herbicide to fall between containers, where it may be more susceptible to transport with runoff water. Gilliam et al (1992) found that the amount of granular herbicide faIling between containers could range from 23 to 80% depending on container placement. Application to individual containers could decrease herbicide losses in runoff because the herbicide has to leach through the substrates to be available for loss in surface runoff (Gilliam et aI.…”
Section: Herhicidementioning
confidence: 99%
“…Wide spacing allows more of a broadcast herbicide to fall between containers, where it may be more susceptible to transport with runoff water. Gilliam et al (1992) found that the amount of granular herbicide faIling between containers could range from 23 to 80% depending on container placement. Application to individual containers could decrease herbicide losses in runoff because the herbicide has to leach through the substrates to be available for loss in surface runoff (Gilliam et aI.…”
Section: Herhicidementioning
confidence: 99%
“…In general, herbicides are applied broadcast over the top of plants in containers with the spaces between containers also receiving herbicide treatment. The loss of granular herbicide formulation outside containers containing no plants was^shown to be 23 to 30% when containers were placed pot to pot and increased to 79 to 80% when contain ers were spaced on 30-cm centers (2). In comparing the effect of a plant in the container when spaced container to container the nontarget losses were 23, 30, and 27% for empty containers, azalea (Rhododendron sp.)…”
Section: Introductionmentioning
confidence: 98%
“…Weed control in container plants is essential due to limited availability of nutrients, water, and space to the ornamental plant. Weeds in containers can reduce the growth of woody ornamentals by nearly 50% in a single growing season (Fretz 1972) and also decrease the aesthetic value of the plant (Gilliam et al 1992). It is estimated that nursery growers spend up to $9,880/ ha on manual removal of weeds in containers depending on weed species (Mathers 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The wide diversity of landscape plant species makes selecting an appropriate herbicide a challenging task (Watkins and Heggers 1982). Up to 80% of broadcast herbicide may settle into spaces between containers (Gilliam et al 1992). Herbicide that falls outside of the containers can leach or move off site with runoff water (Riley et al 1994).…”
Section: Introductionmentioning
confidence: 99%